Second trimester post-abortion family planning uptake and associated factors in 14 public health facilities in Central Uganda: a cross-sectional study - Susan Atuhairwe; Claudia Hanson; Nazarius Mbona Tumwesigye; Kristina Gemzell-Danielsson; Josaphat Byamugisha (BMC, 2023)
Abstract Background Post-abortion family planning counselling and provision are known high impact practices preventing unintended pregnancies. Little is known, however, about specific needs in the second trimester. Our study aims to assess post-abortion family planning uptake and its associated factors among women with second-trimester incomplete abortion. Methods We conducted a cross-sectional survey of 1191 women with incomplete second trimester abortion that received treatment at 14 comprehensive emergency obstetric care public health facilities in central Uganda from August 2018 to November 2021. We computed the post-abortion uptake of family planning within 2 weeks of treatment, described the types of methods accepted, and the reasons for declining family planning. We described the socio-demographic, reproductive, abortion-related, and health facility characteristics. We used mixed effects generalized linear models to obtain percentage differences for factors independently associated with post-abortion family planning uptake. Results Second-trimester post-abortion family planning uptake was 65.6%. Implants (37.5%) and progestin only injectables (36.5%) were the commonly chosen methods; natural (0.1%), permanent (0.8%), and condoms (4%) were the least chosen methods. 45.2% of the women who declined family planning desired another pregnancy soon. Women whose spouses were aware of the pregnancy or had planned pregnancy had 11% (− 10.5, 95% CI − 17.1 to − 3.8) and 12% (− 11.7, 95% CI − 19.0 to − 4.4) less uptake compared to women whose spouses were not aware of the pregnancy or those with unplanned pregnancies respectively. Uptake was 8% (− 7.8, 95% CI − 12.6% to − 3.0%) lower among Islamic women compared to Anglicans. Women who received post-abortion family planning counselling or had more than four live births had 59% (59.4, 95% CI 42.1 to 76.7) and 13% (13.4, 95% CI 4.0 to 22.8%) higher uptake compared to women who did not receive counselling or women with no live births, respectively. Conclusions The uptake of second-trimester post-abortion family planning in Uganda was higher than previous estimates. Post-abortion family planning counselling, grand multiparity, and the need to avoid an unplanned pregnancy enhance post-abortion family planning uptake in the second trimester. Ministry of Health should strengthen post-abortion family planning counselling, especially couple counselling; at all health facilities in the country and also ensure an adequate and accessible supply of a wide contraceptive method mix.